INTERCULTURAL COMMUNICATION KELOMPOK SAMIN DAN MASYARAKAT SEKITAR (OUTGROUP): KAJIAN ANXIETY/UNCERTAINT MANAGEMENT THEORY - Intan Kurnia Syaputri (JURNAL ILMIAH SYI'AR, 2017)
This paper wants to tell about how intercultural communication is intertwined in the community of Samin community and the outside community around the Samin area. The author uses the position of emic approach that sees from the perspective of the Samin group. The author focuses only on the anxiety and uncertainty that occurs. This difference in cultural background certainly affects communication between them. Different cultures and ways of communicating with Samin groups and communities around this Samin may cause various obstacles. Some of the obstacles in question are anxiety and uncertainty between the two parties. Samin groups can be called mindless groups in communicating because Samin groups do not fully pay attention to what they say and do and can not categorize their interlocutors. Samin groups will become mindful when they can be slightly open to information coming from outside the group and acknowledge that there are multiple perspectives for interpreting messages in intercultural communication situations so that communication with outgroups is more effective.